Pengaruh Jenis Ion Logam Berat Terhadap Daya Adsorpsi dan Desorpsi Thermosensitive NIPAM-co-DMAAPS Gel - Eva Oktavia Ningrum; Toni Suharto; Agus Purwanto; Renna Febryanita; Muhammad Sai Firdaus; Sumarno Sumarno; Hikmatun Ni'mah (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
The development of industrial field causes increasing amount of heavy metal ions in the environment. A promising method to deal with the problem above is by utilizing reversible thermosensitive gel as an adsorbent to adsorb heavy metal ions in the environment. The purpose of this research is to develop a reversible thermosensitive gel that able to adsorb heavy metal ions from contaminated water. Copolymergel containing zwitterionic betaine N,N’-dimethyl(acrylamidopropyl) ammonium propane sulfonate (DMAAPS) and thermosensitive N-isopropylacrylamide (NIPAM) copolymer was employed as an adsorbent that able to adsorb and regenerate heavy metal ion in salt solutions. The effect of different ion in various salt solutions and temperature on the adsorption, desorption, and swelling degree of the gel were investigated in this research. The solution used in this experiment are Zn(NO3)2 and Pb(NO3)2 solutions. The gels were synthesized using free radical copolymerization. The synthesized gel showed higher adsorption and desorption ability in Pb(NO3)2 solution than that in Zn(NO3)2 solution. However, gel has a higher value of swelling degree in Zn(NO3)2 solution than that in Pb(NO3)2 solution. Other noticeable result is that swelling degree, desorption, and adsorption ability of the gels decreases in all solution as temperature rises.